2013
DOI: 10.1117/1.jbo.18.10.106006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of measurement on the ballistic–diffusive transition in turbid media

Abstract: The dependence of the transition between the ballistic and the diffusive regimes of turbid media on the experimental solid angle of the detection system is analyzed theoretically and experimentally. A simple model is developed which shows the significance of experimental conditions on the location of the ballistic-diffusive transition. It is demonstrated that decreasing the solid angle expands the ballistic regime; however, this benefit is bounded by the initial Gaussian beam diffraction. In addition, choosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…where μ 0 s ¼ μ s ð1 − gÞ is the reduced scattering coefficient, l tr ¼ 1∕μ 0 s is defined as the transport mean-free path, 20 and g ¼ hcos θi is the mean cosine of the scattering angle (anisotropy factor). 21 When the solid angle δΩ is small, the total transmitted light intensity I can be written as the sum of the number of ballistic photons (I b ) and of a fraction of the diffusive photons (I d ) 22…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…where μ 0 s ¼ μ s ð1 − gÞ is the reduced scattering coefficient, l tr ¼ 1∕μ 0 s is defined as the transport mean-free path, 20 and g ¼ hcos θi is the mean cosine of the scattering angle (anisotropy factor). 21 When the solid angle δΩ is small, the total transmitted light intensity I can be written as the sum of the number of ballistic photons (I b ) and of a fraction of the diffusive photons (I d ) 22…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[15][16][17][18] Recent experiments reveal that the transition length depends not only on the scattering coefficient but on the collecting angle as well. As was later demonstrated experimentally, 19,20 despite its simplicity, this model anticipated the transition from the ballistic regime to the diffusive one with high accuracy. 19,20 It should be stressed that the determination and classification of the transition point are not merely an academic issue.…”
Section: Introductionmentioning
confidence: 73%
“…This model was shown to predict the experimental results, 19,20,34 however, it was shown that there is a discrepancy of a factor of 2 to 4 in the prefactor of the diffusive term.…”
Section: Theoretical Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…It has recently been shown 26 that by applying two simple and well-known modifications, it is possible to substantially extend the ballistic imaging depth of a diffusive medium. This method was based on previous research, 27 which demonstrated that the transition point between the ballistic and diffusive regimes depends not only on the scattering coefficient, but on the collection angle of the detection as well.…”
Section: Introductionmentioning
confidence: 99%